Flexible vs. rigid dieting in resistance-trained individuals seeking to optimize their physiques: A randomized controlled trial - Laurin Alexandra Conlin; Danielle Trina Aguilar; Gavin Elliot Rogers; Bill I Campbell (Taylor & Francis Group, 2021)
Abstract Background The purpose of this study was to compare a flexible vs. rigid diet on weight loss and subsequent weight regain in resistance-trained (RT) participants in a randomized, parallel group design. Methods Twenty-three males and females (25.6 ± 6.1 yrs; 170 ± 8.1 cm; 75.4 ± 10.3 kg) completed the 20-week intervention (consisting of a 10-week diet phase and a 10-week post-diet phase). Participants were randomized to a flexible diet (FLEX) comprised of non-specific foods or a rigid diet (RIGID) comprised of specific foods. Participants adhered to an ~20%kcal reduction during the first 10-weeks of the intervention and were instructed to eat ad libitum for the final 10-weeks. Body composition and resting metabolic rate were assessed 5 times: (baseline, 5, 10 [end of diet phase], 16, and 20 weeks). Results During the 10-week diet phase, both groups significantly reduced bodyweight (FLEX: baseline = 76.1 ± 8.4kg, post-diet = 73.5 ± 8.8 kg, ▲2.6 kg; RIGID: baseline = 74.9 ± 12.2 kg, post-diet = 71.9 ± 11.7 kg, ▲3.0 kg, p < 0.001); fat mass (FLEX: baseline = 14.8 ± 5.7 kg, post-diet = 12.5 ± 5.0 kg, ▲2.3 kg; RIGID: baseline = 18.1 ± 6.2 kg, post-diet = 14.9 ± 6.5 kg, ▲3.2 kg p < 0.001) and body fat% (FLEX: baseline = 19.4 ± 8.5%, post-diet = 17.0 ± 7.1%, ▲2.4%; RIGID: baseline = 24.0 ± 6.2%, post-diet = 20.7 ± 7.1%, ▲3.3%; p < 0.001). There were no significant differences between the two groups for any variable during the diet phase. During the post-diet phase, a significant diet x time interaction (p < 0.001) was observed for FFM with the FLEX group gaining a greater amount of FFM (+1.7 kg) in comparison with the RIGID group (−0.7 kg). Conclusions A flexible or rigid diet strategy is equally effective for weight loss during a caloric restriction diet in free-living, RT individuals. While post-diet FFM gains were greater in the FLEX group, there were no significant differences in the amount of time spent in resistance and aerobic exercise modes nor were there any significant differences in protein and total caloric intakes between the two diet groups. In the absence of a clear physiological rationale for increases in FFM, in addition to the lack of a standardized diet during the post-diet phase, we refrain from attributing the increases in FFM in the FLEX group to their diet assignment during the diet phase of the investigation. We recommend future research investigate additional physiological and psychological effects of flexible diets and weight regain in lean individuals.